Prevalence and correlates of tobacco use amongst junior collegiates in twin cities of western Nepal: A cross-sectional, questionnaire-based survey - Paudel Jagadish; Kishore PV; Sreeramareddy Chandrashekhar T; Menezes Ritesh G (BMC, 2008)
Abstract Background College students are vulnerable to tobacco addiction. Tobacco industries often target college students for marketing. Studies about prevalence of tobacco use and its correlates among college students in Nepal are lacking. Methods A cross-sectional survey was carried out in two cities of western Nepal during January-March, 2007. A pre-tested, anonymous, self-administered questionnaire (in Nepali) adapted from Global Youth Tobacco Survey (GYTS) and a World Bank study was administered to a representative sample of 1600 students selected from 13 junior colleges by two-stage stratified random sampling. Results Overall prevalence of 'ever users' of tobacco products was 13.9%. Prevalence among boys and girls was 20.5% and 2.9% respectively. Prevalence of 'current users' was 10.2% (cigarette smoking: 9.4%, smokeless products: 6.5%, and both forms: 5.7%). Median age at initiation of cigarette smoking and chewable tobacco was 16 and 15 years respectively. Among the current cigarette smokers, 58.7% (88/150) were smoking at least one cigarette per day. Most (67.8%) 'Current users' purchased tobacco products by themselves from stores or got them from friends. Most of them (66.7%) smoked in tea stalls or restaurants followed by other public places (13.2%). The average daily expenditure was 20 Nepalese rupees (~0.3 USD) and most (59%) students reported of having adequate money to buy tobacco products. Majority (82%) of the students were exposed to tobacco advertisements through magazines/newspapers, and advertising hoardings during a period of 30 days prior to survey. The correlates of tobacco use were: age, gender, household asset score and knowledge about health risks, family members, teachers and friends using tobacco products, and purchasing tobacco products for family members. Conclusion School/college-based interventions like counseling to promote cessation among current users and tobacco education to prevent initiation are necessary. Enforcement of legislations to decrease availability, accessibility and affordability of tobacco products and policies to change social norms of tobacco use among parents and teachers are necessary to curb the tobacco use among college students.